Wound healing in older adults with severe burns: Clinical treatment considerations and challenges - Kathleen S. Romanowski; Soman Sen (Elsevier, 2022)
Background: The older adult population continues to rapidly expand in number, with a projection by the United States (US) Census Bureau that there will be more individuals older than > 65 years (77.0 million) than those younger than < 18 years (76.5 million) by 2034. This review provides an overview of aging as it relates to wound healing and burn injuries in older adult patients, summarizes current treatment practices, and addresses the key challenges and considerations for treating severe burn injuries in this specific patient population. Materials and methods: A narrative literature search was conducted, focusing on recent primary literature on burns and wound healing in elderly patients. Results: Studies showed that the aging process results in both physiologic (eg, nutritional and metabolic status) and anatomic changes (eg, thinning dermis) that contribute to a reduced capacity to recover from burn-injury trauma compared with younger patients. Owing to impaired vision, decreased coordination, comorbidities, and medication-induced side effects, older adults (ie, > 65 years) are susceptible to severe burn injury (deep-partial thickness and full-thickness), which is associated with significant morbidity and mortality. Conclusion: A better understanding of the effects of age-related changes regarding wound healing in older adult patients who incur severe burn injuries may provide insight into clinical strategies to improve outcomes among this population.